AYURVEDIC APPROACH FOR THE MANAGEMENT OF KAMALA W.S.R. TO HEPATOCELLULAR JAUNDICE - A CASE STUDY - Astha Shukla; Shiv Shankar Shukla; Bhavana Sharma (International Journal of Ayurveda and Pharma Research, 2019)
Most of the people have become used to spicy fast food day by day. This has taken human being far away from the nature. Nowadays alcohol consumption is also increasing day by day. Ayurvedic texts has mentioned hepatocellular jaundice as Kamala. Ancient Acharyas has also mentioned “kamali tu virechanama” as Chikitsa Sutra for Kamala. Patient was treated with an integrated approach of Ayurvedic treatment including Virechana Karma (purgation) and Shaman Chikitsa. Due to frequently intake of Pittakara Aahara (spicy and hot food), it leads to vitiation of Pitta Dosha and Virechana (purgation) is the first line of treatment for Pittadushti. Due to Ushna, Laghu, Rruksha Guna, and having Tikta -Katu Rasa of Patola, Amrita, Kutaki (ingredients of internal medication) enhances digestive capacity by hepato-protective action and Pittasaraka guna. Ayurvedic line of management i.e. Virechana therapy and Shamana Chikitsa are successful in Kamala by removing toxic waste from the body, and by correction of Agni (digestive fire). In our ancient classics, single drug along with compound drug have been mentioned in Kamala. These drugs have Kamalahara properties. These Ayurvedic formulations relieve the symptom of Daurbalya (weakness), Kshudha mandya (Appetite loss), Pitamutrata (yellow discolouration of urine), Hrullasa (nausea) and Udarshoola. Also these drugs reduce bile in blood circulation and normalize the other blood parameter. Here a case report of a 50 Years male was having Kamala (hepatocellular jaundice) who was treated with some Ayurvedic herbs and Virechana like Panchakarma and get effectively result with Ayurvedic management.